Emerging Roles for Aberrant Astrocytic Calcium Signals in Parkinson’s Disease - Bancroft, Eric A.; Srinivasan, Rahul (Frontiers in Physiology, 2022)
Astrocytes display a plethora of spontaneous Ca2+ signals that modulate vital functions of the central nervous system (CNS). This suggests that astrocytic Ca2+ signals also contribute to pathological processes in the CNS. In this context, the molecular mechanisms by which aberrant astrocytic Ca2+ signals trigger dopaminergic neuron loss during Parkinson’s disease (PD) are only beginning to emerge. Here, we provide an evidence-based perspective on potential mechanisms by which aberrant astrocytic Ca2+ signals can trigger dysfunction in three distinct compartments of the brain, viz., neurons, microglia, and the blood brain barrier, thereby leading to PD. We envision that the coming decades will unravel novel mechanisms by which aberrant astrocytic Ca2+ signals contribute to PD and other neurodegenerative processes in the CNS.